A two-dimensional IB-LBM framework combined with re-tailored RCVM for assessing the rotation intensity of a tornadic wind over a building configuration. (15th January 2017) - Guo, Xixiong; Palanisamy, Rangaraj; Cao, Jun
Highlights: Re-tailored RCVM to render the boundary condition setup more maneuverable. Developed an IB – LBM based computational framework for solving the re-tailored RCVM. Introduced the " critical rotation intensity " for helping characterize tornadoes. Investigated how the critical rotation intensity correlates with the buildings' orientation. Attached importance to the critical rotation intensity for tornado dynamics study. Abstract: A tornado is fundamentally a devastating airflow featuring simultaneous translation and rotation. This hybrid nature makes the simulations more interesting as well as challenging. Numerous laboratorial and computational simulations of tornadoes have been performed in the past few decades to study the tornado dynamics. This study concentrates on the tornado-structure interaction through numerical simulation. Establishing a set of physically-rational and meanwhile computationally-maneuverable boundary conditions for the tornado-building interaction scenario poses a challenge to numerical simulation developers. Inspired by the recent progress in the application of immersed-boundary (IB) lattice Boltzmann method (LBM) to the fluid-structure interaction simulations, this study presents an IB-LBM framework and, meanwhile, revises the renowned Rankine-Combined Vortex Model (RCVM) with the aid of the "relative motion" principle, such that the challenging boundary condition setup issue can be successfully resolved. The present IB-LBM simulations are aimed to investigate the tornado-like wind effects on a building configuration in different orientations and, particularly, seek the relation between the rotation intensity of a tornado and the tornadic wind loadings on the constructions. Through examinations at a series of rotation intensities, the extreme loading value is observed to be unrelated to Reynolds number once the rotation intensity exceeds a critical value. These simulation results reveal that it looks inappropriate to rely solely on the translational velocity component to characterize tornadoes, and call on additional attention towards the rotation intensity for a more comprehensive tornado dynamics study.